Urgent-care antibiotic prescribing: An exploratory analysis to evaluate health inequities. Issue 1 (14th November 2022) - Seibert, Allan M.; Hersh, Adam L.; Patel, Payal K.; Matheu, Michelle; Stanfield, Valoree; Fino, Nora; Hicks, Lauri A.; Tsay, Sharon V.; Kabbani, Sarah; Stenehjem, Edward
Abstract: Healthcare disparities and inequities exist in a variety of environments and manifest in diagnostic and therapeutic measures. In this commentary, we highlight our experience examining our organization's urgent care respiratory encounter antibiotic prescribing practices. We identified differences in prescribing based on several individual characteristics including patient age, race, ethnicity, preferred language, and patient and/or clinician gender. Our approach can serve as an electronic health record (EHR)–based methodology for disparity and inequity audits in other systems and for other conditions.